The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1902/jop.2016.160219
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Treatment Decision Tree and Literature Review of Retrograde Peri‐Implantitis

Abstract: Background: Although retrograde peri‐implantitis (RPI) is not a common sequela of dental implant surgery, its prevalence has been reported in the literature to be 0.26%. Incidence of RPI is reported to increase to 7.8% when teeth adjacent to the implant site have a previous history of root canal therapy, and it is correlated with distance between implant and adjacent tooth and/or with time from endodontic treatment of adjacent tooth to implant placement. Minimum 2 mm space between implant and adjacent tooth is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…Individuals (61 males and 74 females, aged 21 to 89 years; mean age: 61.8 years) provided with implant restorative therapy and undergoing implant maintenance at the Department of Periodontics and Oral Medicine, School of Dentistry, University of Michigan, Ann Arbor, Michigan, between March 1, 2016 and August 31, 2016, were selected for the study. Inclusion criteria were as follows: 1) single or multiple implants placed and restored for >12 months; 2) individuals with/without regular periodontal and/or peri‐implant maintenance; and 3) individuals with/without peri‐implant pathology, such as retrograde peri‐implantitis (radiolucency around implant apex secondary to endodontic lesion), 14 mucositis, and peri‐implantitis.…”
Section: Methodsmentioning
confidence: 99%
“…Individuals (61 males and 74 females, aged 21 to 89 years; mean age: 61.8 years) provided with implant restorative therapy and undergoing implant maintenance at the Department of Periodontics and Oral Medicine, School of Dentistry, University of Michigan, Ann Arbor, Michigan, between March 1, 2016 and August 31, 2016, were selected for the study. Inclusion criteria were as follows: 1) single or multiple implants placed and restored for >12 months; 2) individuals with/without regular periodontal and/or peri‐implant maintenance; and 3) individuals with/without peri‐implant pathology, such as retrograde peri‐implantitis (radiolucency around implant apex secondary to endodontic lesion), 14 mucositis, and peri‐implantitis.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, EMD has been successfully used to treat large periradicular lesions of endodontic origin located adjacently to dental implants with regressive peri-implantitis [145]. Sarnast et al [146] found that regressive peri-implantitis (basically, an endodontic infection from neighbouring teeth) can be treated by initiating infected tooth apicoectomy with dental implant decontamination. This treatment can be performed by EMD application which aids in periapical lesion healing.…”
Section: Emdogain and Its Use In Dental Fieldmentioning
confidence: 99%
“…Previous studies reported an incidence of 0.26% for RPI, 36 increasing to 7.8% if adjacent teeth had previous root canal therapy 7 and 13.6% if the tooth extracted had a periapical lesion 15 . Other studies showed the chance of RPI occurring in an implant adjacent to a tooth with an apical lesion to be about 25% (OR = 8.0) 37 …”
Section: Discussionmentioning
confidence: 99%
“…Epstein‐Barr virus is occasionally associated with the pathogenesis of symptomatic periapical lesions in endodontically involved teeth and should likewise be expected to play a role when implants are placed in the same sites 44 . Additionally, an HIV‐related infection had been described as an etiological factor for RPI as well 37 …”
Section: Discussionmentioning
confidence: 99%